2012
DOI: 10.1093/scan/nss013
|View full text |Cite
|
Sign up to set email alerts
|

Why are you looking like that? How the context influences evaluation and processing of human faces

Abstract: Perception and evaluation of facial expressions are known to be heavily modulated by emotional features of contextual information. Such contextual effects, however, might also be driven by non-emotional aspects of contextual information, an interaction of emotional and non-emotional factors, and by the observers’ inherent traits. Therefore, we sought to assess whether contextual information about self-reference in addition to information about valence influences the evaluation and neural processing of neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 74 publications
9
99
0
1
Order By: Relevance
“…Our current finding that even everyday dynamic textures, such as streaming water, swirling leaves, moving clouds, waving flags or traffic streams can influence perceived facial dominance agrees with the growing body of evidence that background context modulates perceived facial emotions(Koji 2010 [5] )(Lee 2012 [6] )(RIGHART 2008 [7] ). The current results also agree with recent brain studies showing that contextual information influences activities in the extended neural network of face processing and thereby alters the perception and evaluation of facial expressions(Schwarz 2012 [12] )(Van den_Stock_2013 [13] )(Wieser 2012 [8] ) (Wieser 2014 [14] ). In particular, it was recently observed that the amygdala integrates facial expression with salient motion information(Hindi Attar_2010 [15] ).…”
Section: Resultssupporting
confidence: 92%
“…Our current finding that even everyday dynamic textures, such as streaming water, swirling leaves, moving clouds, waving flags or traffic streams can influence perceived facial dominance agrees with the growing body of evidence that background context modulates perceived facial emotions(Koji 2010 [5] )(Lee 2012 [6] )(RIGHART 2008 [7] ). The current results also agree with recent brain studies showing that contextual information influences activities in the extended neural network of face processing and thereby alters the perception and evaluation of facial expressions(Schwarz 2012 [12] )(Van den_Stock_2013 [13] )(Wieser 2012 [8] ) (Wieser 2014 [14] ). In particular, it was recently observed that the amygdala integrates facial expression with salient motion information(Hindi Attar_2010 [15] ).…”
Section: Resultssupporting
confidence: 92%
“…Herbert, Herbert, Ethofer, and Pauli (2011), for example, paired unpleasant, pleasant and neutral words with the possessive pronouns "my" or "his" in order to indicate self-or other reference. They found that the late positive potential was enhanced for unpleasant nouns only when preceded by personal pronouns , In an fMRI study, Schwarz, Wieser, Gerdes, Mühlber-ger, and Pauli (2012) presented sentences with varying contextual information (e.g., "she thinks you are incompetent" vs. "he thinks you are competent") followed by neutral faces given their ambiguous nature (Schwarz et al, 2012). Results revealed strong effects of self-reference on the activation of the medial prefrontal and right +fusiform gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results are among the first to show how social affect cues can influence cognitive control (see also e.g. Park and Kitayama 2014;Schwarz et al 2013). The findings have broader implications for our understanding of interactions between error-processing mechanisms and social affect processing.…”
Section: Discussionmentioning
confidence: 82%